Integrated approach using petrophysical, gravity, and magnetic data to evaluate the geothermal resources at the Rahat Volcanic Field, Saudi Arabia - Alqahtani, Faisal; Ehsan, Muhsan; Aboud, Essam; Abdulfarraj, Murad; El-Masry, Nabil (Frontiers in Earth Science, 2023)
It is necessary to develop and explore geothermal resources to achieve sustainable development and clean renewable energy around the Globe. Geothermal energy is crucial to the future energy supply to meet the environmentally friendly energy demand of the World. The Rahat Volcanic Field (Kingdom of Saudi Arabia) is the oldest and lengthiest Cenozoic Volcanic Field in the World. It is a dominantly a mature mafic Volcanic Field that holds three major geological events; the historic eruption (1256 C.E.), the five fingers (~4500–1500 BP), and the seismic swarm (1999 C.E.). These incidents were studied by utilizing geological information and geophysical data sets. Geophysical and geostatistical research includes gravity and magnetic survey data, including different log curves and major elements, obtained from water samples as well as of volcanic rocks obtained by X-ray fluorescence (XRF). To gain an understanding of the subsurface thermal structure, these datasets were analyzed. The primary goal of this study is to identify the prominent potential geothermal resources with the help of an available data set. Findings suggest that beneath the historic eruption site along with the fissure eruption, on the western side, there is a geothermal anomaly with a surface footprint of about 35 km2. Analyzing gravity and magnetic data as well as density and magnetic susceptibility variations in rock samples led to the mapping of this anomaly. It has been inferred through integrated study that statistical analysis of major elements will be helpful to validate the results of the outcome.